Plasma oxytocin changes and anti-obsessive response during serotonin reuptake inhibitor treatment: a placebo controlled study - Humble, Mats B (BioMed Central, 2013)
BACKGROUND: The drug treatments of choice for obsessive-compulsive disorder (OCD) are serotonin reuptake inhibitors (SRIs). However, a correlation between the neuropeptide oxytocin in cerebrospinal fluid and the severity of OCD has previously been shown, and oxytocin and serotonin are interconnected within the brain. Few studies have investigated whether SRIs have any effect on oxytocin; thus, our aim was to explore the possibility that oxytocinergic mechanisms contribute to the anti-obsessive effect of SRIs. METHOD: In a randomized, double-blind trial, comparing SRIs (clomipramine and paroxetine) with placebo in 36 adults with OCD (characterized for subtypes), plasma oxytocin was measured with radioimmunoassay after plasma extraction, at baseline, after 1 week, and after 4 weeks of treatment, and related to baseline severity and clinical response after 12 weeks, as measured by the Yale-Brown Obsessive Compulsive Scale (Y-BOCS). RESULTS: Baseline oxytocin levels correlated positively with baseline Y-BOCS ratings, but only among the future SRI responders. Patients with early onset of OCD had higher baseline oxytocin. During treatment, plasma oxytocin did not differ between SRI and placebo treatment. In SRI responders, plasma oxytocin first decreased and then increased; in non-responders (to SRI as well as to placebo), the reverse was the case. After 4 weeks, treatment responders had attained higher oxytocin levels compared to non-responders. The intra-individual range (i.e. the variability) of plasma oxytocin between measurements was the measure that best differentiated responders from non-responders. This range was higher in responders than non-responders, and lower in patients with autistic traits. CONCLUSIONS: SRIs have highly variable effects on plasma oxytocin between individuals. The associations between baseline oxytocin and OCD severity and between oxytocin changes and treatment response support the notions that oxytocin is involved in OCD pathophysiology, and that the anti-obsessive effects of SRIs are partly exerted through oxytocinergic mechanisms.